Consumer Behavior as The Main Key in Online Purchase in A Growing Marketplace - Safira, Adelia; Astuti, Puji (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Marketplace is an internet-based online media (web based) where business activities and transactions between buyers and sellers are carried out. This study aims to determine the relationship of perceived risk, purchase intention, perceived benefit, actual purchase and attitude in consumer online buying and selling transactions based on behavior in a developing marketplace in Indonesia. This research was conducted in andJakarta, Bogor, Depok, Tangerang, Bekasi in January 2023. The data collection process was carried out by distributing online questionnaires through social media. Furthermore, this study used purposive sampling method to determine respondents. This research was conducted on 273 online shopping consumers at Shopee/Tokopedia/Lazada. The data obtained was analyzed using the structural equation model (SEM) method. The results of this study show a negative effect of perceived risk and a positive attitude towards online purchase intention. Furthermore, the perceived benefit is not proven to have a positive effect on online purchase intention and actual purchase. Finally, perceived risk does not negatively affect actual purchases. Suggestions for further research can expand the objects and respondents of research, change sampling and add or change variables.